A glimmer of hope: pro-environmental behavior increases positive emotions after confrontation with environmental threat - Zeier, Peter; Lange, Florian; Rowland, Zarah; Wessa, Michèle; Wenzel, Mario (Journal of environmental psychology, 2025)
When confronted with ecological crises, people may experience a variety of emotions ranging, e.g., from fear to anger and guilt. The increasing prevalence of eco-emotions raises the question of how to manage these emotional states. Although individuals can choose from a variety of emotion regulation strategies, some strategies have been found to thwart pro-environmental behavior. In a series of experimental studies, we examined the emotion regulation potential of pro-environmental behavior itself. Participants in exploratory Studies 1a and 1b were presented a text about the loss of biodiversity and then decided how much time to spend on an effort task that yields donations to an environmental organization. More pro-environmental behavior was associated with an increase in hope and a decrease in fear in both studies and a decrease in guilt in Study 1b. However, more pro-environmental behavior was confounded with a greater time interval between emotional ratings. In preregistered Study 2, we controlled for possible cool-down effects by having participants complete a time-limited task that would either yield donations to an environmental organization or have no pro-environmental consequences after reading the biodiversity text. Similar to Studies 1a and 1b, participants in the pro-environmental behavior group compared to the control group reported a stronger increase in hope. However, both groups reported a similar decrease in fear and guilt. Consistent with previous research, pro-environmental behavior seems especially effective in upregulating positive emotions. Drawing hope from pro-environmental behavior while maintaining a certain level of concern and responsibility is discussed as an adaptive emotional response to environmental threat.
Gesehen am 03.11.2025